Gentrification and Displacement: The Forced Relocation of Public Housing Tenants in Inner-Sydney - Morris, Alan (SpringerBriefs in Sociology,, 2019)
This book examines the forced displacement of public housing residents in Sydney's Millers Point and The Rocks communities. It considers the strategies deployed by the government to pressure tenants to move, and the social and personal impacts of the displacement on the residents themselves. Drawing on in-depth interviews with tenants alongside government and media communications, the Millers Point case study offers a penetrating and moving analysis of gentrification and displacement in one of Australia's oldest and more unique working class and public housing neighbourhoods. Gentrification and Displacement advances work in urban studies by charting trends in urban renewal and displacement, furthering our understanding of public housing, gentrification and the effects of forced relocation on vulnerable urban communities.